Airway narrowing assessed by anatomical optical coherence tomography in vitro: Dynamic airway wall morphology and function - Noble, P.; West, A.; McLaughlin, R.; Armstrong, J.; Becker, S.; McFawn, P.; Williamson, J.; Eastwood, Peter; Hillman, D.; Sampson, D.; Mitchell, H. (The American Physiological Society, 2010)
Regulation of airway caliber by lung volume or bronchoconstrictor stimulation is dependent on physiological, structural, and mechanical events within the airway wall, including airway smooth muscle (ASM) contraction, deformation of the mucosa and cartilage, and tensioning of elastic matrices linking wall components. Despite close association between events in the airway wall and the resulting airway caliber, these have typically been studied separately: the former primarily using histological approaches, the latter with a range of imaging modalities. We describe a new optical technique, anatomical optical coherence tomography (aOCT), which allows changes at the luminal surface (airway caliber) to be temporally related to corresponding dynamic movements within the airway wall. A fiber-optic aOCT probe was inserted into the lumen of isolated, liquid-filled porcine airways. It was used to image the response to ASM contraction induced by neural stimulation and to airway inflation and deflation. Comparisons with histology indicated that aOCT provided highresolution images of the airway lumen including mucosal folds, the entire inner wall (mucosa and ASM), and partially the cartilaginous outer wall. Airway responses assessed by aOCT revealed several phenomena in "live" airways (i.e., not fixed) previously identified by histological investigations of fixed tissue, including a geometric relationship between ASM shortening and luminal narrowing, and sliding and bending of cartilage plates. It also provided direct evidence for distensibility of the epithelial membrane and anisotropic behavior of the airway wall. Findings suggest that aOCT can be used to relate changes in airway caliber to dynamic events in the wall of airways. Copyright © 2010 the American Physiological Society.